Neuromarketing dalam Perspektif Etika Bisnis Islam: Antara Inovasi dan Manipulasi - Musaffa, Muhamad Ulul Albab; Tamtowi, Moh; Syarifah, Zetty (UIN Sunan Kalijaga, 2023)
The development of neuromarketing as an interdisciplinary approach that integrates neuroscience, psychology, and marketing has created new opportunities for a more precise understanding of consumer behavior. However, from the perspective of Islamic business ethics, an academic problem arises regarding the boundary between legitimate innovation and manipulative practices that harm consumers. Techniques such as scarcity and dark patterns raise serious concerns because they risk undermining the principles of justice, contractual clarity, and consumer consent, which are fundamental in Islamic commercial jurisprudence. This study seeks to examine the position of neuromarketing by referring to the framework of maqāṣid al-sharī‘ah, particularly the dimensions of ḥifẓ al-‘aql (protection of intellect), ḥifẓ al-māl (protection of wealth), and ḥifẓal-nafs (protection of self), alongside relevant fiqh principles. The research employs a library-based method with a critical analytical approach. Data were collected from contemporary neuromarketing literature, consumer ethics studies, and classical sources in Islamic jurisprudence. The analysis was carried out through a dialectical engagement between modern research findings and Islamic normative principles, resulting in an evaluative synthesis. The findings indicate that neuromarketing can be categorized as a halal by design practice when it is directed towards clarifying information, enhancing consumer literacy, and strengthening transparency. Conversely, it becomes manipulative when it exploits consumer cognitive biases. The primary contribution of this research is the formulation of the Shariah Neuromarketing Ethics Index (SNEI) as an ethical audit instrument applicable to the development of the halal marketing industry in the digital era.